STATE AND PROSPECTS OF INNOVATIVE AND INVESTMENT DEVELOPMENT OF DOMESTIC TRADE IN THE CONDITIONS OF POST-WAR ECONOMIC TRANSFORMATION (INNOVATIVE ECONOMY, 2026)
Karpenko V.L., Zakryzhevska I.V.  STATE AND PROSPECTS OF INNOVATIVE AND INVESTMENT DEVELOPMENT OF DOMESTIC TRADE IN THE CONDITIONS OF POST-WAR ECONOMIC TRANSFORMATIONPurpose. The aim of the article is to examine the functioning of Ukraine's domestic trade and outline promising directions for its innovation and investment development in the context of post-war economic transformation based on an analysis of modern challenges, digitalization trends, financial and investment support, and institutional modernization of the industry.Methodology of research. The methodological basis of the study is a systematic approach, methods of analysis and synthesis, comparison, generalization, statistical, structural and logical analysis. The systematic approach was used to assess the impact of war and post-war transformations on the functioning of domestic trade in Ukraine. Comparative analysis was used to study the features of the development of the trade sector in crisis and recovery periods. The structural and logical approach provided the definition of promising directions for the innovation and investment development of domestic trade. The generalization of scientific works, analytical materials and regulatory documents made it possible to form comprehensive conclusions regarding the prospects for modernization of the industry in the conditions of post-war economic recovery.Findings. The study revealed that domestic trade in Ukraine has suffered significant losses due to military actions, including infrastructure destruction, disruption of logistics chains, declining consumer demand, and labour shortages. At the same time, a high level of adaptability of the trade sector was identified, manifested through the implementation of digital technologies, the development of energy independence, business relocation, and the modernization of logistics processes. The key role of omnichannel strategies, mobile commerce, cloud technologies, immersive digital solutions, and socially responsible business models in creating competitive advantages for trade enterprises was substantiated. The importance of implementing the electronic consignment note (e-CMR/e-TTN), expanding war-risk insurance mechanisms, and using state credit programmes and international financial instruments to stimulate innovative and investment development of the sector was proved.Originality. A comprehensive approach to studying the state of innovation and investment development of domestic trade in Ukraine is substantiated, which is based on a combination of digital transformation, financial and investment support, development of energy independence and institutional adaptation to European Union standards. Provisions on the use of state and international support instruments to minimize military risks and ensure sustainable development of domestic trade in the post-war period have been further developed.Practical value. The results of the study can be used by public authorities in the formation of policies aimed at the recovery and development of domestic trade, the design of innovative and investment support programs for enterprises and the improvement of logistics digitalization and war-risk insurance mechanisms. The proposed recommendations can be applied by business entities to increase operational efficiency, strengthen competitive positions, and ensure sustainable development under the conditions of post-war economic transformation.Key words: domestic trade, institutional regulation, innovative and investment development, post-war economic recovery, public regulatory policy.
Keywords: domestic trade; institutional regulation; innovative and investment development; post-war economic recovery; public regulatory policy